A highly bioavailable curcumin formulation ameliorates inflammation cytokines and neurotrophic factors in mice with traumatic brain injury - Sakul, Ayse Arzu; Balcikanli, Zeynep; Ozsoy, Nilay Ates; Orhan, Cemal; Şahin, Nurhan; Tuzcu, Mehmet; Şahin, Kazım (Wiley, 2024)
A novel curcumin formulation increases relative absorption by 46 times (CurcuWIN (R)) of the total curcuminoids over the unformulated standard curcumin form. However, the exact mechanisms by which curcumin demonstrates its neuroprotective effects are not fully understood. This study aimed to investigate the impact of a novel formulation of curcumin on the expression of brain-derived neurotrophic factor (BDNF), glial fibrillary acidic protein (GFAP), a main component of the glial scar and growth-associated protein-43 (GAP-43), a signaling molecule in traumatic brain injury (TBI). Mice (adult, male, C57BL/6j) were randomly divided into three groups as follows: TBI group (TBI-induced mice); TBI + CUR group (TBI mice were injected i.p. curcumin just after TBI); TBI+ CurcuWIN (R) group (TBI mice were injected i.p. CurcuWIN (R) just after TBI). Brain injury was induced using a cold injury model. Injured brain tissue was stained with Cresyl violet to evaluate infarct volume and brain swelling, analyzed, and measured using ImageJ by Bethesda (MD, USA). Western blot analysis was performed to determine the protein levels related to injury. While standard curcumin significantly reduced brain injury, CurcuWIN (R) showed an even greater reduction associated with reductions in glial activation, NF-kappa B, and the inflammatory cytokines IL-1 beta and IL-6. Additionally, both standard curcumin and CurcuWIN (R) led to increased BDNF, GAP-43, ICAM-1, and Nrf2 expression. Notably, CurcuWIN (R) enhanced their expression more than standard curcumin. This data suggests that highly bioavailable curcumin formulation has a beneficial effect on the traumatic brain in mice. The use of curcumin is limited due to its poor bioavailability. A novel curcumin formulation with 46 times higher absorption than standard curcumin was tested in TBI. A novel curcumin formulation (CurcuWIN) increased BDNF, GAP-43, ICAM-1, and Nrf2 levels in the brain. Curcumin may have potential therapeutic properties for treating brain injuries in mice.image
Keywords: curcumin; inflammation; neurotrophic factor; traumatic brain injury